Analysis of corporate governance and corporate sustainability performance in the Indonesian context - Suharyono; Zarefar, Arumega; Zarefar, Atika (Business: Theory and Practice, 2023)
This study aims to examine the effect of corporate governance on the Corporate sustainability performance. The samples of this study consist of publicly-traded primary and secondary sector companies in Indonesia for eleven years, from 2010 to 2020. This study discusses the effect of corporate governance on corporate sustainability performance, Corporate governance, and corporate sustainability performance. The data used in the study are hand-collected data sourced from annual financial and company sustainability reports. The findings of the study indicate that Corporate Governance (CG) is positively affecting the Corporate Sustainability Performance (CSP) and its dimensions (Economy, Environmental, and Social aspects) significantly. Furthermore, the findings of the study have also disclosed that the CG elements consisting of the rights of shareholders (Category A), The equitable treatment of shareholders (Category B), The role of stakeholders in corporate governance (category C), disclosure principles and transparency (category D), and the responsibilities of the board (Category E) relatively showing positive effects significantly towards the CG and its elements. However, different effects have been found in the elements B and D, where it is showing that the sample companies indicate the weaknesses in the practice of the equitable treatment of shareholders and Disclosure and transparency. This study is expected to contribute to or assist the companies’ policymakers by creating regulations to improve the Corporate sustainability performance. Our research adds to the research on corporate governance and Corporate sustainability performance in analyzing the correlation between CG and CSP deeply and broadly by utilizing the instruments according to the developed OECD principles.